이미지를 활용한 오디오-비쥬얼 시스템 구성 - 서준석(June-Seok Seo); 홍성대(Sung-Dae Hong); 박진완(Jin-Wan Park) (한국콘텐츠학회 논문지, 8(6), 2008)
With the help of information technology The problem of building a concrete form with a shapeless media is the starting point of presenting information by means of sound. Audio-Visual System using sound as a medium is a method that presents an auditory material visually and has a role of linking different sensory organs. In a sense, Audio-Visual System transfers a non-concrete sensation to a concrete one. Audio-Visual System presentation by late methods using active and non-active images produced by computerized irregular procedures can be limited because of the limited ways of visual output. On the other side, visualization using active images can induce more diverse expressions using sound as a medium. This study suggests a new way of expression in animations using visualization of various auditory materials and sounds built by Audio-Visual System with active images. 소리를 이용한 정보의 표현 방법은 무형의 특징을 가진 매체를 이용하여 어떠한 방법을 통하여 구체적인 형태를 이끌어 내는가에 대한 문제에서 시작된다. 이 과정에서 소리를 매개체로 이용하여 구성되는 오디오-비쥬얼 시스템은 청각적 소재를 이용한 시각적 표현이라는 방법적 측면에서 감각 기관의 연계에 대한 역할을 맡고 있는 부분에서 청각의 시각화라는 비 구체적 감각에 대한 구체화라는 변형의 의미를 갖는다. 오디오-비쥬얼 시스템 형태를 통한 작품을 표현하는데 있어 기존에 사용되던 프로그래밍을 통한 비규칙적 프로시쥬얼(Procedure)적 동적(動的) 이미지 또는 비동적(非動的) 이미지를 사용한 표현 방법에서 시각적 출력 방법의 제한으로 인한 표현 방법의 제한이 생겨날 수 있는 부분에 있어 동적 이미지를 이용한 오디오-비쥬얼 시스템을 통하여 소리를 매체로 한 다양한 표현 결과물을 이끌어낼 수 있다. 본 논문에서는 동적 이미지를 사용한 오디오-비쥬얼 시스템을 통해 다양한 청각적 소재의 시각화 방법 및 소리를 이용한 애니메이션 표현법의 새로운 대안을 제시한다.